Pengaruh Variasi Media terhadap Motivasi Belajar Siswa pada Mata Pelajaran Sejarah Kelas XI IPS SMA Negeri 8 Pekanbaru - Thasya Maleno; Bedriati Ibrahim; Asril Asril (LP4MK STKIP PGRI Lubuklinggau, 2022)
SMA Negeri 8 Pekanbaru is one of the public high schools which was originally SMPP 49 Pekanbaru and was founded in January 1976 by the minister of Education and culture on November 26, 1975 Number 0261/0/1975. This study aims to determine the effect of the use of media variations on student motivation in the history subject of class XI IPS SMA Negeri 8 Pekanbaru. The type of research used in this study is quantitative type. This research was conducted at SMA Negeri 8 Pekanbaru starting from the submission of the proposal until the completion of the thesis by the author. The use of learning media in history is able to reconstruct the final period that is shrouded in obscurity. The subject of this research was students of SMA Negeri 8 Pekanbaru, namely class XI IPS which collected 100 students. The analysis uses the classical aspect of interest. Media learning history also makes history come alive, clear, and relevant to the lives of students who are oriented to the present or the future. This research was conducted at SMA Negeri 8 Pekanbaru in class XI IPS with a simple of 100 students to fill out a questionnaire or questionnaire that has been provided. The results of this study indicate that the research that has been carried out on the effect of media variations on students’ learning motivations in learning history in class XI IPS at SMA Negeri 8 Pekanbaru, the authors can make the following conclusions, the results of the study indicate that the implementation of media variations in history learning is good, proven by the perception of each student said is a relationship between the media variation program and the motivation to learn history at SMA Negeri 8 Pekanbaru.